Analisis Pengaruh Dimensi Jingle Iklan Sepeda Motor Honda Beat di Televisi Terhadap Keputusan Pembelian di Wilayah Perkotaan Jember - Ayunda Nurul Nirmala; Adi Prasodjo; Ketut Indraningrat (UPT Penerbitan Universitas Jember, 2014)
The research aimes to analyse the impact of jingle of Honda Beat motorcycle advertisement on buying decision in Jember . This research used independent variable that consist of memorability, meaningfulness, likability, adaptability and protectability as the dimension of jingle and buying decision as the dependent variable. This research used logistic regression analysis. The sampling method was a non-probability sampling. Using a purposive sampling, 100 respondents of the citizen of Jember were selected. The results showed that memorability influenced Honda Beat motorcycle buying decision. Whereas, meaningfulness, likability, adaptability and protectability did not influence the buying decision. This results mean that any increase in memorability on Honda Beat jingle advertising will increase in the probability of the buying decision on Honda Beat motorcycle.